Heterotrophic Bio-Oil Production From Microalgae - Çağlar, Emre; Bayraktar, Oğuz (Izmir Institute of Technology, 2010)
The purpose of the thesis is to investigate the parameters affecting heterotrophic production of microalga, Chlorella minutissima. The aim is to use crude glycerol, a waste product derived from biodiesel production, as a carbon and energy source for microalgal growth and examine the optimum growth conditions in chemostat mode, as well as the productivity of oil using FTIR based technique. The highest lipid productivity achieved was 1.04 gl-1h-1, at the temperature 250C, with the dilution rate of 0.25 h-1 and using a substrate concentration of 80 gl-1 in feeding medium. The lipid, protein and carbohydrate content at this conditions was 14.36%, 47.89% and 8.06%, respectively.
Thesis (Master)--Izmir Institute of Technology, Energy Engineering, Izmir, 2010
Includes bibliographical references (leaves: 28-32)
Text in English; Abstract: Turkish and English
viii, 41 leaves
Keywords: Biomass energy; Microalgae--Biotechnology